Armistice and Germany's food supply 1918-19 : a study of conditional surrender - Menne, Bernhard (London: Hutchinson & Co.; New York; Melbourne, 1944)
"by Bernhard Menne ; foreword by Charles Jarman Bibliotheek Camille Huysmans"